ARTISTIC ANALYSIS OF HANDCRAFTED HORSES DEDICATED TO LOKDEVTA BABA RAMDEVJI - Manish; Sharma, Dr. Renu (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The land of Rajasthan has always been world famous as the mother of folk art and folk deities. The folk deity of western Rajasthan, baba ramdevji has been famous for his miracle. Devotees ask from baba ramdevji for the completion of any of their special tasks. On the fulfillment of the request, devotees offer horses made of cloth according to their reverence. In this context, work is being done to make various types of small and big artistic horses from cloth to offer to baba Ramdevji in Pratap Nagar area of Jodhpur district. This work of making horses is being done not only in Jodhpur but also in Jaisalmer, Ramdevra and Pokaran. Horses are adorned with grass thatch, white and colorful cloth, garland, core, turiya, tassel of wool etc. symbols of the artistic workmanship of the handicrafts. The size, stature and gracefulness of these horses give the feel of real horses. According to the Hindu Calendar, artistic horses made of cloth have special significance in this fair, which lasts from second to tenth of day of Shuklapaksha of August month. Where not only Rajasthan but people from many states of India like Gujarat, Madhya Pradesh etc. come to see them. The ancient tradition of offering a horse here in the from of faith and belief is unbroken, which is being followed even in today’s modern era. The artistic horses of cloth being offered as Manauti are folk art tradition and cultural importance as well as a great means of earing livelihood of the handicraftsmen.